Fatal acute hepatic failure secondary to thrombotic portal venopathy after commencing abemaciclib and fulvestrant treatment for advanced breast carcinoma: a unique autopsy finding. Issue 7 (14th May 2021) - Haynes, Harry R; Mohan, Vivek; Mozayani, Behrang; Gallagher, Patrick
Abstract: We present an autopsy case of hepatic thrombotic portal venopathy resulting in decompensated liver failure and death which occurred rapidly after commencing abemaciclib and fulvestrant chemotherapy for advanced invasive lobular carcinoma of the breast. The diagnosis was confirmed histologically. This is the first reported case of such a finding. We suggest that further cases displaying this previously unpublished pattern are collated in order that we may begin to investigate the underlying etiological mediators.